Attaining interprofessional competencies by connecting oral health to overall health. Issue 4 (23rd November 2020) - Haber, Judith; Hartnett, Erin; Cipollina, Jessamin; Allen, Kenneth; Crowe, Ruth; Roitman, Janna; Feldman, Lauren; Fletcher, Jason; Ng, Grace
Abstract: Purpose: The purpose of this study was to evaluate the effectiveness of an annual oral‐systemic health interprofessional education (IPE) clinical simulation and case study experience with nurse practitioner/midwifery (NP/MW), dental (DDS), medical (MD), and pharmacy (PharmD) students. Methods: The Interprofessional Collaborative Competency Attainment Scale (ICCAS) was used to measure students' self‐reported attainment of interprofessional competencies before and after the IPE experience. Pre‐ and post‐test surveys were completed by NP/MW, DDS, MD, and PharmD student cohorts from 2017 to 2019. Students also had the opportunity to provide qualitative feedback about their experience at post‐test. Data were collected from IPE faculty facilitators to assess their perception of the value of the Teaching Oral‐Systemic Health (TOSH) program. Results: Student ICCAS results demonstrated statistically significant improvement in self‐reported interprofessional competencies among all types of students across all 3 years ( P < 0.001); qualitative student comments reflected positive experiences with the TOSH program. Survey data from IPE faculty facilitators supported the value of the IPE experience for all students. Conclusions: The findings demonstrate the effectiveness of the TOSH program in using oral‐systemic health as a clinical exemplar to develop interprofessional competencies. The 2017–2019 data reinforce the credibility of scaling the TOSH model for developing interprofessional competencies with students from different health professions.